Efecto de la tintura de huacatay (Tagetes Minuta) para el tratamiento de gingivitis en caninos domésticos (Canis Lupus Familiaris - Ayala Cuvi, Liliana Elizabeth (Ecuador : Latacunga: Universidad Técnica de Cotopaxi (UTC), 2021)
The aim of this research was to determine the effect of Huacatay (Tagetes minuta) tincture for the treatment of gingivitis in domestic canines (Canis lupus familiaris). 20 canines were treated at random from the "El Corralito" veterinary clinic, and were subjected to the application of the tincture in two treatments prior to the laboratory report of positive bacteria in the oral cavity. The technique used was experimental by means of t Student analysis. To estimate its effectiveness, a clinical record was made for follow-up and a buccal swabbing of the gum for the collection of bacterial samples. Two groups of 10 canines were made, T1, application of Huacatay Tincture twice a day every day for 30 days and T2, application of Huacatay Tincture once a day, twice a day for 30 days, on the 15th and 30th days new samples were taken to determine the bacterial CFU. The results obtained from the investigation concluded that the gram-positive bacteria Staphylococcus spp, Staphylococcus coagulase negative, Staphylococcus aureus, Streptococcus spp, Streptococcus beta haemolyticus, Bacillus spp and Enterobacter cloacae (gram-negative) had a percentage of effectiveness of (100%) T1 and T2, except Escherichia coli (gram-negative) which was (63%) in T1 and in T2, (100%). The biochemical analysis of the Huacatay tincture was carried out using the chromatography method, giving a result of 5368.75 milligrams of catechins per litre of tincture. It was concluded that catechins form the active principle of the Huacatay plant and act by inhibiting bacterial glycosyl transferases, preventing their adherence and nutrition La presente investigación tuvo como finalidad determinar el efecto de la tintura de Huacatay (Tagetes minuta) para el tratamiento de Gingivitis en caninos domésticos (Canis lupus familiaris), se trataron 20 caninos al azar de la clínica veterinaria “El Corralito”, estos se sometieron a la aplicación de tintura en dos tratamientos precedente al informe de laboratorio positivos a bacterias en cavidad bucal. La técnica ...